Pengaruh Hadis dan Kekuatan Spiritual terhadap Sultan Muhammad Al-Fatih dalam Penaklukan Konstantinopel - Fauziah Nurdin (Forum Intelektual Qur'an dan Hadits Asia Tenggara (SEARFIQH) Kota Banda Aceh, 2022)
Constantinople is the most important city in the world, it was founded in 330 AD by the Byzantine emperor, Constantine I. The city has a number one position internationally. Since its founding, the Byzantines have made it the capital of their country. Therefore, Muhammad Al-fatih tried to be able to conquer Constantinople in order to realize the hadith of the Prophet Muhammad